Low‐Molecular‐Weight Polymer with CO2‐Switchable Surface Activity. Issue 6 (10th June 2021) - Zhu, Zhuoyan; Huang, Xiaoling; Hou, Qingfeng; Sun, Zhitao; Su, Xin; Quan, Hongping
Abstract: The introduction of external CO2 could reversibly convert tertiary amines into quaternary ammonium salts, enabling demulsification/emulsification switching of emulsions or latexes. However, CO2 ‐switchable oligomeric or low‐molecular‐weight polymeric surfactants are rarely researched. In this study, 2‐(dimethylamino)ethyl methacrylate and stearyl methacrylate are chosen to synthesize a switchable oligomeric surfactant (OS). The conductivity of OS aqueous solution (0.2 wt%) increased from 14.0 to 329 μS cm −1 by adding and removing CO2, which proved a good performance of OS in response to the CO2 stimulus. The most important finding was that the crude oil emulsion containing OS was reversibly degraded and re‐formed by the alternate CO2 and N2 treatment. In contrast to that, the investigated PS latex system underwent apparent stratification after the N2 bubbling, but it regained a homogeneous phase upon the N2 bubbling. The particle size of PS latex varied between 245 nm and 130 μm, and zeta potential changed from −43.2 to −5.8 mV, which demonstrated that the PS latex stability might break and recover by addition and removal of CO2 . This work is expected to open a new window for the CO2 ‐stimulated reversible emulsification of emulsions or polymer latexes.